Minimal Invasive Dynamic Hip Screw Fixation for Intertrochanteric Fractures of Femur - Kandel, Prakriti Raj; Pathak, Laxmi; Singh, Gyaneshwar Prasad; Baral, Rajiv (Journal of Universal College of Medical Sciences, 2018)
INTRODUCTION: Good results have been achieved consistently with compression hip screw fixation for stable intertrochanteric femur fractures by conventional method. Thus, this present study was conducted to find out the outcomes for such hip fracture fixation with minimal invasive technique. MATERIALS AND METHOD: This retrospective study was carried out by collecting the records of 66 adult patients with stable intertrochanteric femur fracture managed by Dynamic Hip Screw (DHS) fixation with minimal invasive technique under Spinal Anaesthesia and Epidural Analgesia in Universal College of Medical Sciences and Teaching Hospital (UCMSTH) over a period of 3 years. The patients were in follow up visits for 1 year postoperatively. Operating time, blood loss, decrease in haemoglobin level, analgesic demand, length of hospital stay, fracture union time, early and delayed complications and functional outcome were recorded. RESULTS: This study showed less operative time, less blood loss and less reduction in mean haemoglobin value postoperatively when compared with baseline values. Though complications like pain, stitch infection at surgical site and UTI was seen in few patients, all patients were mobilized within 2nd postoperative day with less rescue analgesic demand and shorter duration of hospital stay of only 8.23 days. However, plate breakage, nonunion, implant cut out, joint infection, delayed union and varus deformity was not observed in any of these patients. Moreover, Harris Hip Score showed good functional outcome.CONCLUSION: Fixation of DHS with minimal invasive technique for stable hip fracture has good functional outcome in cost effective way with fewer incidences of complications.Journal of Universal College of Medical Sciences (2016) Vol.04 No.01 Issue 13, Page: 26-31